SUKUH TEMPLE IN KARANG ANYAR CENTRAL JAVA - Riyanti, Menul Teguh (International Journal of Engineering Technologies and Management Research, 2018)
In the Majapahit royal government all elements including culture in the lives of the people, such as sculpture, literary arts, and stage art must all be religious. One of the very unique and specific relics of the Majapahit Kingdom is the Sukuh temple in Central Java, the uniqueness of the temple relief depicting the symbol of human reproduction. Sukuh Temple is a Hindu temple in Majapahit era located in Central Java, located in Sukuh Hamlet, Berjo Village, Ngargoyoso District, Karanganyar Regency, Central Java Province. The reason for choosing the title of Sukuh Temple has a feature that is not found in other temples, especially temples in Java especially. The aim is that the specialty and uniqueness of the Sukuh temple as one of the relief of the heyday of the Majapahit Kingdom This research aims to examine the functions and meanings of the depicting reliefs as a symbol of Hinduism found in Sukuh Temple. Relief findings contained in the Sukuh temple are manifestations of the gods glorified by Hindus so that they are highly sacred. The reliefs included lingga and yoni, garuda reliefs (garudeya stories), head reliefs, and turtle statues. The functions and meanings that are very prominent in the Sukuh Temple are symbols of lingga and yoni, believed to be a symbol of fertility, because it is believed that the origin of life originated from the meeting of two genitals, male and female.